New evidence on income distribution and economic growth in Japan - Masako Oyama (Osaka University, Institute of Social and Economic Research (ISER), 2014)
There have been many theoretical and empirical researches on the effects of income distribution on economic growth. This paper uses Japanese prefectural panel data to empirically analyze how income distribution affects economic growth. Four measures of the income distribution are used in the system GMM estimations. The Gini indices, income share of the third quintile and the ratio of the income share of the top decile and the 5th decile show that income inequality has negative effects on growth. The ratio of the income share of the bottom decile and the 5th decile does not have statistically significant effects. Therefore, the estimation results show that the increased income inequality in recent Japan decreased the economic growth.
Keywords: O40; C33; J01; 330